Impact Factors of Empathy in Mainland Chinese Youth - Zhao, Qing; Ren, Qiaoyue; Sun, Yuanmiao; Wan, Li; Hu, Li (Frontiers in Psychology, 2020)
Empathy was investigated in 592 Mainland Chinese youth using the Interpersonal Reactivity Index. Participants’ empathy-related information covering demographic traits, emotional wellness, as well as academic and social problems were recorded. Results of Classification and Regression Tree (CART) analysis showed that emotional empathy, cognitive empathy, and empathy-related personal distress was impacted by inherited traits (e.g., sex), acquired traits (e.g., study major), and a combination of both aspects, respectively. Moreover, empathy was found to be higher in youth in a vulnerable social position (i.e., outlander, female, and ethnic minority) than those in a dominant one (i.e., local, male, and ethnic majority). It was also found that personal distress, rather than empathy, was significantly correlated with academic, social, and emotional problems in the cohort of youth. Hence, the current study provided an innovative observation of the relationships between empathy, personal distress, ethnicity, social vulnerability, wellness, study major, and other key characteristics in Mainland Chinese youth.